(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rangga KK, Yonariza, Yanfika H, Mutolib A. 2020. Perception, attitude, and motive of local community towards forest conversion to plantation in Dharmasraya District, West Sumatra, Indonesia. Biodiversitas 21: 4903-4910. Forest conversion in Dharmasraya District massively occurred from 2000 to 2014. In 2000, forest area reached 86% of 33,550 ha. In 2014, forest cover reduced to only 16% with an increase in plantation area (rubber and oil palm), covering 59% of the total area. This study was aimed to examine the perception, attitude, and motive of the local community regarding forest conversion to the plantation. This study was located in PFMU (Production Forest Management Unit) Dharmasraya West Sumatra, which included a production forest area. This study was conducted from February to August 2018 with a case study approach. A total of 40 households, was selected as respondents. Snowball sampling was applied to interview the key informants. Data were analyzed using the interactive model, which included data reduction, data presentation, also conclusion drawing and verification. The study result indicated that forest is owned by the local community based upon the customary law, and the state does not have the right to manage and claim forest ownership. In terms of the economic aspect, the community benefited greatly from wood availability in the forest as the source of income. According to the local community, the conversion of forests into plantation did not have a significant effect on the environment. In fact, the local community agreed that land-use change from forest to plantation will provide greater benefit than preserving the forest. The expansion of plantation was found to be the motive for land clearance by cutting trees to obtain ownership over the forest.